Isolated Dissection of the Ductus Arteriosus Associated with Sudden Unexpected Intrauterine Death - Marny Fedrigo; Silvia Visentin; Paola Veronese; Ilaria Barison; Alessia Giarraputo; Erich Cosmi; Gaetano Thiene; Maria Teresa Gervasi; Cristina Basso; Annalisa Angelini (Journal of Cardiovascular Development and Disease, 2021)
We report five cases of sudden intrauterine death due to premature closure of the ductus arteriosus. In four cases, this was caused by dissecting the hematoma of the ductus arteriosus with intimal flap and obliteration of the lumen. In one case, the ductus arteriosus was aneurysmatic, with lumen occlusion caused by thrombus stratification. No drug therapy or free medication consumption were reported during pregnancy. The time of stillbirth ranged between 26 and 33 gestational weeks. We performed TUNEL analysis for apoptosis quantification. The dissecting features were intimal tears with flap formation in four of the cases, just above the origin of the ductus arteriosus from the pulmonary artery. The dissecting hematoma of the ductus arteriosus extended downward to the descending aorta and backward to the aortic arch with involvement of the left carotid and left subclavian arteries. TUNEL analysis showed a high number of apoptotic smooth muscle cells in the media in two cases. Abnormal ductal remodeling with absence of subintimal cushions, lacunar spaces rich in glycosaminoglycans (cystic medial necrosis), and smooth muscle cell apoptosis were the pathological substrates accounting for failure of remodeling process and dissection.